2018
DOI: 10.1175/jhm-d-18-0005.1
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Climate Change, CO2, Land-Use Change, and Human Activities to Changes in River Flow across 10 Chinese Basins

Abstract: As an essential source of freshwater river flow comprises ~80% of the water consumed in China. Per capita water resources in China are only a quarter of the global average, and its economy is demanding in water resources; this creates an urgent need to quantify the factors that contribute to changes in river flow. Here, we used an offline process-based land surface model (ORCHIDEE) at high spatial resolution (0.1° × 0.1°) to simulate the contributions of climate change, rising atmospheric CO2 concentration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…Numerous studies focused on assessing the impacts of environmental changes on runoff [26,27,61,63]. Investigating the effects of environmental changes on runoff usually involves the application of hydrologic models [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies focused on assessing the impacts of environmental changes on runoff [26,27,61,63]. Investigating the effects of environmental changes on runoff usually involves the application of hydrologic models [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…CC BY 4.0 License. ORCHIDEE does not include the irrigation effect on the soil moisture, ET, and vegetation growth, although the model can simulate this anthropogenic pressure (Xi et al, 2018). The snow processes are described using a 3-layer scheme of intermediate complexity (Wang et al, 2013), in which the snow albedo and insulating properties depend on the snow density and age.…”
Section: Ecvsmentioning
confidence: 99%
“…Other human activities, such as damming, groundwater withdrawal, water consumption, and land use change, can have substantial impacts on R of the river basin [55,56]. Land-use change accounts for <0.2% of the change in the runoff trend [57], while damming, groundwater withdrawal, and water consumption account for <2%, <1%, and <10% of the changes in the annual runoff [58], respectively. However, other research studies have indicated climate change as the main factor affecting R (accounting for 90% of the change in R in the YRB) [57,59,60,61].…”
Section: Introductionmentioning
confidence: 99%